Physicochemical characterization of used coconut oil from vacuum frying of jackfruit (Artocarpus heterophyllus Lam) pulp Eviarc sweet variety as affected by frying cycle - Braga, Jason D.; Lauzon, Roberta D.; Galvez, Lorina A. (2019)
This study was conducted to determine the quality of coconut oil (CO) used in a 2-h jackfruit pulp vacuum frying for 20 frying cycles. The % free fatty acid (FFA), acid value (AV), peroxide value (PV), moisture content (MC), and color of the CO used in vacuum frying was determined for unheated oil and oil after the 1st, 5th, 10th, 15th, and 20th cycle of frying. The FFA (0.273?0.554%), AV (0.543?1.102 NaOH/kg oil), PV (4.983?45.739 meq oxygen/kg), and MC (1.016?1.079%) showed significant increase (p <0.05) in the oil as the number of frying cycle increased that dictated the quality of the used CO. Hunter L and b showed significant (p < 0.05) effect on oil as the number of frying cycle increases, while Hunter a indicated insignificant effect. Based on the standard set by the Codex Alimentarius Commission (CAC) for refined CO (10 meq O2/kg oil), the oil quality is still safe after the third frying cycle, which conforms with the set standards for PV and AV. The pairing of these two tests is a good measure of oil quality assessment. (Author's abstract)
Includes bibliographical references (pages 593-595)
Keywords: Coconut oil; Moisture content; Physicochemical quality; Recycling of oil